Analisis Hukum Perlindungan Data Pribadi dalam System Cloud Computing - Tobi Haryadi (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The rapid development of information technology has encouraged the adoption of cloud computing as a data storage and management solution. However, the use of this technology poses challenges in the protection of personal data, especially from a legal perspective. This study analyses the protection of personal data in cloud computing based on the applicable legal framework, both at the national and international levels. The main focus of this study includes the principles of data protection, the obligations of cloud service providers, the rights of users, as well as legal challenges in the enforcement of personal data protection. The results show that although there are regulations governing the protection of personal data, there are still legal gaps and challenges in their implementation, especially regarding jurisdiction, service provider responsibilities, and data security. Therefore, it is necessary to improve regulations and cooperation between various parties to ensure more optimal protection of personal data in the cloud computing environment.